Distraction or Learning Tool? Social Media Influence on BBA Students' Academic Performance - Mehta, Amlesh; Parajuli, Kewal Ram; Pokhrel, Shantanu (Journal of Research and Development, 2026)
The rapid growth of internet accessibility and social networking platforms has significantly transformed the academic and social lives of university students. Social media platforms such as Facebook, Instagram, YouTube, TikTok, and WhatsApp are widely used by students for various purposes. While social media offers opportunities for learning and collaboration, excessive and unstructured use has raised concerns regarding its impact on students’ academic performance. Despite widespread use, limited research exists on the combined effect of usage duration and purpose among BBA students in Dhankuta. This study aims to examine usage patterns, perception and the relationship between social media use and academic performance of university students. The study adopted a descriptive and analytical research design and was based on both primary and secondary data. Primary data were collected through a structured questionnaire administered to 52 BBA students selected while secondary data were obtained from books, online journals, and previous research reports. Convenience sampling was adopted due to time constraints and ease of access to respondents. The findings reveal that all respondents actively use social media and possess multiple social media accounts. A majority of students spend two hours or more per day on social media, with usage being highest during evening and late-night hours. Entertainment was identified as the primary purpose of social media use, whereas academic use was relatively limited. Analysis of academic performance shows that students who spend less time on social media tend to achieve higher SGPA, while those spending more time especially for non-academic purposes generally have lower or average academic performance. Correlation analysis indicates a very weak relationship (r = 0.0984) between time spent on social media and academic performance. Suggesting that academic outcomes are influenced not only by usage duration but also by the purpose and manner of use. Overall, the study concludes that social media has a mixed but predominantly negative impact on academic performance when used excessively and without academic focus. The study recommends promoting responsible, balanced, and academically oriented use of social media can contribute to improved academic outcomes.